Opinions of Middle School Students on the Justice Concept within the Framework of Social Studies Education - Oguz Hacat, Sibel (Sciedu Press, 2018)
The aim of this study is to reveal the opinions of middle school students about the justice concept.  The study was carried out in accordance with the document review technique, which is one of the qualitative research methods. The study group consists of 82 students attend in 7th grade receiving education at a middle school in the city of Kastamonu in the school year 2016-2017. Data was obtained using semi-structured interviews consisting of open-ended questions. This data was interpreted using content analysis and by way of coding. Middle school students’ opinions on justice concept are represented in 8 different categories and they use 7 different sayings relating to the justice concept. Whereas the justice concept is most often explained as “Rightfulness”, it is least often conceived as “Abstinence from Committing Crimes”. It is observed that the saying “Justice can do what swords cannot” is used by middle school students most often, and the saying “No merit can be more noble than justice” least often. In light of this information, middle school students can be provided with environments in which they can internalize the justice concept. Furthermore, results about justice can be drawn when its content is broadened. We can do scientific study about justice in more detail by increasing sample group.
Keywords: 4. Education; 16. Peace & justice